(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2022)
Israel is leader in rescue missions around the world, while Latin America and the Caribbean is the second most disaster-prone region. This thesis compares and analyses 2 Israeli humanitarian missions sent to Mexico and Brazil in 2017 and 2019, respectively. With this analysis we were able to answer our main question: Is it convenient for Israel to send humanitarian missions on every disaster that occurs in Latin American countries and what are the implications in diasporic relations settings? This research was conducted with a qualitative approach based on case studies. Data was collected by observation and in-depth interviews with 3 experts on the field. With all the collected information we built an evaluation matrix to work as a guide or checklist for future Israeli humanitarian missions in Latin America. Our analysis shows that both cases did not follow the same patterns for execution, and as well did not bring out the same outcomes. Throughout the whole research ask ourselves if it is convenient for Israel to send humanitarian aid on every disaster that occurs in Latin American countries. The answer in short is yes, but it is worth exploring the long version by reading this research. We conclude that Israel is a global leader in humanitarian missions, which does not mean that is not necessary for the missions to follow a protocol to protect the receiving countries, the reputation of the helping country and the relations between the parties involved.